Evolution in novel environments: Do restored prairie populations experience strong selection?. Issue 10 (21st July 2020) - Magnoli, Susan M.; Lau, Jennifer A.
Abstract: When populations colonize new habitats, they are likely to experience novel environmental conditions, and as a consequence may experience strong selection. While selection and the resulting evolutionary responses may have important implications for establishment success in colonizing populations, few studies have estimated selection in such scenarios. Here we examined evidence of selection in recently established plant populations in two prairie restorations in close proximity (<15 km apart) using two approaches: (1) we tested for evidence of past selection on a suite of traits in two Chamaecrista fasciculata populations by comparing the restored populations to each other and their shared source population in common gardens to quantify evolutionary responses and (2) we measured selection in the field. We found evidence of past selection on flowering time, specific leaf area, and root nodule production in one of the populations, but detected contemporary selection on only one trait (plant height). Our findings demonstrate that while selection can occur in colonizing populations, resulting in significant trait differences between restored populations in fewer than six generations, evolutionary responses differ across even nearby populations sown with the same source population. Because contemporary measures of selection differed from evolutionary responses to past selection, our findings also suggest that selection likely differs over the early stages of succession that characterize young prairies.